Освітлення робочого місця програміста - Ахременко, В. О. (ХНУРЕ, 2019)
In this work, the illumination norms of the workplace of the programmer, as a person working behind a computer, are given. It is told how to identify problems with illumination in the workplace. On the example of two companies considered ways to solve these problems. Considered natural and artificial illu-mination. It is also described how measurements were made. Attention is paid to the professional disease of a programmer associated with improper organization of the workplace, and specifically insufficient or excessive illumination.